THE THREE DIMENSIONAL ASPECTS OF THE MAIN CHARACTER OF THE GREAT GATSBY - Sang Ayu Isnu Maharani (International Journal of Linguistics and Discourse Analytics, 2020)
This study aims to describe the three dimensional aspects of the main character of ‘The Great Gatsby’ novel as well as the function of his character. The data used for this study is The Great Gatsby novel; it is a well-known novel written by F. Scott Fitgerald in 1925. The study applied the three dimensional character by Egri Lajoz (1985) supported by Wellek and Warren (1966).The supporting theory applied is taken from Morner and Rausch (1991) to analyze the function of the character. The Great Gatsby novel comprises of nine chapter and was written in 1925 by F. Scott Fitgerald, one of prominent author in the Modern Period of history of literature. The data were collected by observation method and the technique applied was note taking. The novel was read thoroughly and the lines describing the dimensional aspect of the main characters were highlighted, and later categorized. The data was analyzed descriptively by applying the qualitative method. The finding shows that the three dimensional aspects are as follow: The Physiological aspect shows that Jay Gatsby is an elegant person, around thirty, handsome and has polite yet mysterious manner. The sociological aspect shows that Gatsby is a man with reputable status and wealthy. The psychological aspect shows that Gatsby is a narcissist, a person who has extreme idealism about getting his true love returning to him after he is being wealthy, a liar as the consequences of repression of his genuine identity who grows up in a poor family